Bimbingan Orang Tua Berbasis Family Resilience Untuk Meningkatkan Minat Baca Al-Qur’an Pada Anak Di Desa Latimojong - susanto, juneadi dwi susanto; Mukmin (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2024)
Parental guidance based on family resilience is a relevant concept in increasing children’s interest in reading the Koran. The aim of this research is to increase family resilience in families in educating and developing healthy productive forces in every adaptation to the environment. The research method used is qualitative. With the results of research on family resilience-based parental guidance, we found patterns in educating children, such as providing direction, providing examples or examples, showing children’s habits and needs in reading the Al-Qur’an, providing an understanding of the importance of reading the Al-Qur’an, good communication towards children. Keywords: Parental Guidance, Family Resilience, Reading Interest